2021
DOI: 10.1039/d0cp04811a
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment effects of ionic liquid mixtures at polarized electrode interfaces monitored by potential screening

Abstract: The interface of electrodes and IL mixtures has been studied by in situ XPS. We found that the concentration of counterions at the interface can strongly deviate from the bulk composition due to interactions between electrode and IL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…That experimental setup enabled the formation of a liquid film thin enough to probe the IL/electrode interface such that the authors were able to follow the EDL processes by tracing the shifts in the core-level binding energies under bias. While the application of direct current (DC) bias during XPS data acquisition provides steady-state information, demonstrated by us and others as well, our group has previously shown that alternating current (AC) excitation is indispensable for investigation of the dynamics of electrical potential developments. Use of scanning electron microscopy (SEM) for detecting similar changes due to potential induced intensity modulations was also recently reported by us . Both our XPS and SEM investigations revealed that the effects of time-resolved polarization of the metal electrodes can be followed locally up to extremely long-distance (centimeters) and long-time (hundreds of seconds) ranges, in a chemically specific fashion.…”
Section: Introductionsupporting
confidence: 58%
“…That experimental setup enabled the formation of a liquid film thin enough to probe the IL/electrode interface such that the authors were able to follow the EDL processes by tracing the shifts in the core-level binding energies under bias. While the application of direct current (DC) bias during XPS data acquisition provides steady-state information, demonstrated by us and others as well, our group has previously shown that alternating current (AC) excitation is indispensable for investigation of the dynamics of electrical potential developments. Use of scanning electron microscopy (SEM) for detecting similar changes due to potential induced intensity modulations was also recently reported by us . Both our XPS and SEM investigations revealed that the effects of time-resolved polarization of the metal electrodes can be followed locally up to extremely long-distance (centimeters) and long-time (hundreds of seconds) ranges, in a chemically specific fashion.…”
Section: Introductionsupporting
confidence: 58%
“…Ionic liquids are excellent candidates as new non-aqueous electrolytes that can be used in fuel cells, capacitors and batteries. 72 Since typical by-products of ionic liquid synthesis are halides and metal salts that interfere dramatically with the electrochemical properties of the molten salt, 73 the use of the halide-free and metal-free dialkylcarbonate route is particularly suited to the preparation of ionic liquids for these applications.…”
Section: Potential Uses Of the Dialkyl Carbonate Routementioning
confidence: 99%
“…To investigate the fundamentals of these processes, researchers have used techniques such as electrochemical methods, microscopy, terahertz imaging, and X-ray analysis, often complemented by modeling and simulations. , Still, every technique has its own shortcomings when it comes to replicating real-world electrochemical devices. Another tool often utilized for deeper insight is X-Ray Photoelectron Spectroscopy (XPS). Over the course of several years, our research group has harnessed the power of XPS to delve into the intricate details of ionic liquid/metal interfaces. XPS, renowned for its exceptional surface sensitivity, enables us to unravel some of the chemical and electronic properties of the samples and/or devices.…”
Section: Introductionmentioning
confidence: 99%